Effectiveness of Snakehead Fish (Channa striata) Snacks in Improving Protein Intake and Albumin Levels in Adolescent Girls at Risk of Chronic Energy Deficiency - Annasari Mustafa; Dwie Soelistyorini; Astutik Pudjirahaju; Puput Dewi Safitri (Knowledge Dynamics, 2024)
Background: Chronic Energy Deficiency (CED) is a condition characterized by long-term inadequate intake of energy and protein, identified through Mid-Upper Arm Circumference (MUAC) measurements with a threshold of less than 23.5 cm. According to the 2013 Riskesdas data, the prevalence of CED among individuals aged 15-19 years in Indonesia was 46.6%, which decreased to 36.3% in 2018 for non-pregnant women. In East Java, the prevalence of CED among 15-19-year-olds was 52.5% in 2013 and 37.73% in 2018. Despite this decline, low albumin levels often signal poor nutritional status, typically resulting from prolonged nutrient deficiencies. Snakehead fish (Channa striata), known for its high protein content, particularly albumin, offers a potential solution for improving protein intake and blood albumin levels among adolescent girls at risk of CED. In this study, snacks made from snakehead fish provide significant protein, including 216.1 kcal and 8.01g of protein (Nugget), 214.88 kcal and 13.76g of protein (Siomay), and 216.4 kcal and 7.8g of protein (Ekado). When combined with vegetables, these snacks are expected to improve nutritional values, especially protein and albumin levels. This study aims to assess the impact of snakehead fish (Channa striata)-based snacks on protein intake and blood albumin levels in adolescent girls at risk of CED. Methods: The study used an experimental, quasi-experimental design with a one-group pretest-posttest approach. The intervention was provided twice a week for 2 months, with monitoring through 24-hour food recall forms and food records. Results: The results showed a significant improvement in protein intake (p = 0.009, paired sample T-test) and blood albumin levels (p = 0.000, Wilcoxon test) after the intervention. Conclusion: Snakehead fish (Channa striata)-based snacks effectively enhance protein intake and blood albumin levels in adolescent girls at risk of CED.